Expanding the genetic toolbox for the obligate human pathogen Streptococcus pyogenes - Lautenschläger, Nina; Schmidt, Katja; Schiffer, Carolin; Wulff, Thomas F.; Hahnke, Karin; Finstermeier, Knut; Mansour, Moïse; Elsholz, Alexander K. W.; Charpentier, Emmanuelle (Frontiers in Bioengineering and Biotechnology, 2024)
Genetic tools form the basis for the study of molecular mechanisms. Despite many recent advances in the field of genetic engineering in bacteria, genetic toolsets remain scarce for non-model organisms, such as the obligatory human pathogen Streptococcus pyogenes. To overcome this limitation and enable the straightforward investigation of gene functions in S. pyogenes, we have developed a comprehensive genetic toolset. By adapting and combining different tools previously applied in other Gram-positive bacteria, we have created new replicative and integrative plasmids for gene expression and genetic manipulation, constitutive and inducible promoters as well as fluorescence reporters for S. pyogenes. The new replicative plasmids feature low-and high-copy replicons combined with different resistance cassettes and a standardized multiple cloning site for rapid cloning procedures. We designed site-specific integrative plasmids and verified their integration by nanopore sequencing. To minimize the effect of plasmid integration on bacterial physiology, we screened publicly available RNA-sequencing datasets for transcriptionally silent sites. We validated this approach by designing the integrative plasmid pSpy0K6 targeting the transcriptionally silent gene SPy_1078. Analysis of the activity of different constitutive promoters indicated a wide variety of strengths, with the lactococcal promoter P23 showing the strongest activity and the synthetic promoter PxylS2 showing the weakest activity. Further, we assessed the functionality of three inducible regulatory elements including a zinc-and an IPTGinducible promoter as well as an erythromycin-inducible riboswitch that showed low-to-no background expression and high inducibility. Additionally, we demonstrated the applicability of two codonoptimized fluorescent proteins, mNeongreen and mKate2, as reporters in S. pyogenes. We therefore adapted the chemically defined medium called RPMI4Spy that showed reduced autofluorescence and enabled efficient signal detection in plate reader assays and fluorescence microscopy. Finally, we developed a plasmid-based system for genome engineering in S. pyogenes featuring the counterselection marker pheS*, which enabled the scarless deletion of the sagB gene. This new toolbox simplifies previously laborious genetic manipulation procedures and lays the foundation for new methodologies to study gene functions in S. pyogenes, leading to a better understanding of its virulence mechanisms and physiology.